2002
DOI: 10.1300/j082v42n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, Alcohol, and Civil and Rough Conflict Resolution Strategies in Lesbian Couples

Abstract: The present study investigated the relations among testosterone level, acute alcohol consumption, and the use of violent (Rough) or non-violent (Civil) conflict resolution strategies in lesbian couples. The participants were 54 lesbian campers at a women's campground or spectators at a gay pride celebration who each provided a saliva sample for testosterone assay and completed a questionnaire. On the questionnaire, participants indicated whether they used Civil or Rough tactics to deal with domestic discord, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Although demographic characteristics and sexual identity and mental health factors (e.g., post-traumatic stress disorder and problematic alcohol use) had significant associations with IPV perpetration, they were no longer statistically significant after accounting for IPV victimization. However, other studies have found that alcohol and other drug use are important correlates of IPV perpetration among SMW (Baker et al, 2002; Fortunata & Kohn, 2003; Lewis et al, 2018).…”
Section: Resultsmentioning
confidence: 86%
“…Although demographic characteristics and sexual identity and mental health factors (e.g., post-traumatic stress disorder and problematic alcohol use) had significant associations with IPV perpetration, they were no longer statistically significant after accounting for IPV victimization. However, other studies have found that alcohol and other drug use are important correlates of IPV perpetration among SMW (Baker et al, 2002; Fortunata & Kohn, 2003; Lewis et al, 2018).…”
Section: Resultsmentioning
confidence: 86%
“…Alguns autores analisam a violência também dentro dos próprios grupos LGBT, dessacralizando o grupo e tirando o foco apenas da sua vitimização (BAKER et al, 2002;KUEHNLE & Sullian, 2003;Speziale et al, 2006;WALTERS, 2009;TURNER, 2009;FINNERAN & STEPHESON, 2013). Uma observação interessante assinalada por Lamble (2013) é que, em vários países, os grupos LGBT, que antes se colocavam como vítimas e procrastinados, partiram para exigir a criminalização daqueles que os discriminam, colocando a questão sexual dentro de uma lógica punitiva.…”
Section: Avanços Nos Direitos E Persistências Nos Preconceitosunclassified